Hilah dalam Jual Beli pada Sistem Al-Ijarah Al-Muntahiya Bit Tamlik Perspektif Hukum Ekonomi Syariah (Studi Kasus BMT UGT Nusantara Capem Pujer) - Ubaidillah, Ubaidillah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Sekolah Tinggi Islam Blambangan (STIB) Banyuwangi, 2023)
The use of three contracts, namely buying and selling, IMBT, and grants implemented by BMT UGT Nusantara is the background of this research. Before entering into an IMBT contract, a customer who applies for financing must first sell goods to the BMT using a sale and purchase agreement. This is very contradictory when combined with DSN-MUI Fatwa No. 27/DSNMUI/III/2002 concerning Ijarah Mutahiyah Bit Tamlik. The qualitative descriptive method that the researcher used to explain the implementation of the Al-Ijarah Al-Muntakiyah bit Tamlik contract in financing BMT UGT Nusantara. While the data collection procedure uses observation and interviews. Data were analyzed by using triangulation analysis techniques. We can draw the results of this discussion as the thread that the implementation of Ijarah Muntahiyah Bit Tamlik in the BMT UGT Nusantara financing product Pujer sub-branch is in accordance with the principles of muamalah. However, the Ijarah Al Muntakiyah Bit Tamlik contract practiced by BMT UGT Nusantara has a slight difference according to the standardization of permissibility in the book Fiqh Al Buyu'. However, the implementation and other procedures are very much aligned with the DSN-MUI Fatwa No. 27/DSNMUI/III/2002 concerning the Ijarah Al Mutahiyah Bit Tamlik contract.